Note on a Class of Subsets of AG(3, q) with Intersection Numbers 1, q and n with respect to the Planes. (22nd December 2013) - Napolitano, Vito
Abstract : We give a new and correct proof of a result of O. Ferri and S. Ferri (1995) on q 2 -caps of AG ( 3, q ) in this paper; moreover we prove that sets of AG ( 3, q ) of type ( 1, q, q + 1 ) with respect to the planes of AG ( 3, q ) have size at most q 2 with equality if and only if 𝒦 is a cap.